Retrospective Radiographic Evaluation of Ridge Dimensional Changes After Vertical Augmentation Using the Novel Wide-Head Tent Pole Screw Technique - Nam-Suk Yoon; Hyunsuk Choi; Hyung-Gyun Kim; Dong-Seok Sohn (Journal of Functional Biomaterials)
Introduction: Although significant advancements have been made in surgical techniques for reconstructing severely resorbed alveolar bone, achieving predictable regeneration remains a considerable challenge. Many conventional ridge augmentation methods require extended edentulous healing periods and multiple surgical interventions. This clinical study introduces a simplified approach to advanced ridge augmentation using a wide-head tent-pole screw (WHTPS), aimed at enhancing procedural efficiency and achieving predictable clinical outcomes. Material and Methods: Thirteen patients with severely vertically resorbed mandibular segments or completely edentulous alveolar ridges—each presenting with a minimum vertical bone defect of 5 mm—were included in this study. A single WHTPS was placed at the most severe bone defect site, followed by bone grafting and coverage with a resorbable membrane. Postoperative panoramic radiographs were taken immediately after surgery and again on the day of WHTPS removal, following a healing period of 3 to 6 months. An additional follow-up radiograph was obtained after final prosthesis placement, with an average follow-up period of 5.5 months, to assess changes in the augmented bone. Patients were monitored clinically for a period ranging from 8 to 20 months (mean: 14.9 months). Results: The average vertical bone gain immediately after surgery was 8.86 mm (SD ± 2.59 mm), while an average bone resorption of 1.49 mm (17.79%) was observed during the follow-up period. Conclusions: A single WHTPS effectively stabilized the graft material in cases of severe alveolar bone loss, thereby preventing its resorption and displacement. Further clinical studies are necessary to validate its long-term effectiveness.